BZIP71 delays flowering by suppressing Ehd1 expression in rice. Issue 7 (14th June 2022) - Li, Xiufeng; Tian, Xiaojie; He, Mingliang; Liu, Xinxin; Li, Zhiyong; Tang, Jiaqi; Mei, Enyang; Xu, Min; Liu, Yingxiang; Wang, Zhenyu; Guan, Qingjie; Meng, Wei; et al.
ABSTRACT: Flowering time is a fundamental factor determining the global distribution and final yield of rice ( Oryza sativa ). Although diverse flowering time genes have been reported in this crop, the transcriptional regulation of its key flowering genes are poorly understood. Here, we report that a basic leucine zipper transcription factor, bZIP71, functions as a flowering repressor. The overexpression of bZIP71 delays flowering, while the bzip71 mutant flowers early in both long‐day and short‐day conditions. A genetic analysis showed that the regulation of flowering by bZIP71 might be independent of Heading date 2 (Hd2), Hd4, and Hd5. Importantly, bZIP71 directly associates with the Early heading date 1 ( Ehd1 ) promoter and represses its transcription, and genetically the function of bZIP71 is impaired in the ehd1 mutant. Moreover, bZIP71 interacts with major components of polycomb repressive complex 2 (PRC2), SET domain group protein 711 (SDG711), and Fertilization independent endosperm 2 (FIE2), through which bZIP71 regulates the H3K27me3 level of Ehd1 . Taken together, we present a transcriptional regulatory mechanism in which bZIP71 enhances the H3K27me3 level of Ehd1 and transcriptionally represses its expression, which not only offers a novel insight into a flowering pathway, but also provides a valuable putative target for the genetic engineering and breeding of elite rice cultivars. Abstract : bZIP71 functions as a flowering repressor in rice and recruits Polycomb Repressive Complex 2 to the Early heading date1 locus, enhancing H3K27me3 levels and repressing expression.